2017
DOI: 10.3847/1538-3881/aa72df
|View full text |Cite
|
Sign up to set email alerts
|

Debiasing the NEOWISE Cryogenic Mission Comet Populations

Abstract: We use NEOWISE data from the four-band and three-band cryogenic phases of the Wide-field Infrared Survey Explorer mission to constrain size distributions of the comet populations and debias measurements of the shortand long-period comet (LPC) populations. We find that the fit to the debiased LPC population yields a cumulative size−frequency distribution (SFD) power-law slope (β) of −1.0±0.1, while the debiased Jupiter-family comet (JFC) SFD has a steeper slope with β=−2.3±0.2. The JFCs in our debiased sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 51 publications
10
61
2
1
Order By: Relevance
“…A more recent determination of the debiased LPC SFD is significantly shallower than our distribution with α = 0.200 ± 0.014 for 1 km < D < 20 km (Bauer et al, 2017). It is difficult to reconcile this value with our slope because, even allowing for the combined statistical+systematic uncertainty in our value ( §3.3.5), the two values differ by 3-σ.…”
Section: Corrected Lpc Size Distributioncontrasting
confidence: 76%
See 1 more Smart Citation
“…A more recent determination of the debiased LPC SFD is significantly shallower than our distribution with α = 0.200 ± 0.014 for 1 km < D < 20 km (Bauer et al, 2017). It is difficult to reconcile this value with our slope because, even allowing for the combined statistical+systematic uncertainty in our value ( §3.3.5), the two values differ by 3-σ.…”
Section: Corrected Lpc Size Distributioncontrasting
confidence: 76%
“…For this reason there are perhaps only a dozen or so reliable LPC nucleus size measurements (Meech, 2017b) obtained from radar observations (e.g. Harmon et al, 1997), or where it was possible to model and remove the coma because of high resolution Hubble Space Telescope data (Meech et al, 2004), or space-based thermal-IR measurements (Bauer et al, 2017(Bauer et al, , 2015. Bauer et al (2015) suggested on the basis of measurements from the WISE observatory that the known, active LPCs were on average about twice as large as the short-period comets, but they did not have a large sample and the measurements were not corrected for observational selection effects.…”
Section: Introductionmentioning
confidence: 99%
“…For centaurs, an ensemble analysis gives a mean albedo of 8% ± 4% (Stansberry et al 2008;Bauer et al 2013), which is consistent with diameters between ∼10 and 14 km. NEOWISE provided an independent diameter estimate for P/2010 TO20 of 10.6 km (Bauer et al 2017, see online data).…”
mentioning
confidence: 99%
“…Recent studies have shown that the total number of long-period comets in the inner solar system is far higher than was hitherto thought, perhaps by as much as a factor of 10 (Bauer et al, 2017) [3].…”
Section: Long-period Cometsmentioning
confidence: 98%